Experimental characterisation and computational modelling of cyclic viscoplastic behaviour of turbine steel. (July 2019) - Rae, Y.; Benaarbia, A.; Hughes, J.; Sun, W.
Graphical abstract: Highlights: High temperature creep-fatigue characterisation is conducted on an aged turbine steel. A unified temperature- and rate-dependent viscoplastic model is presented and implemented into Abaqus code. Material parameters are derived using an optimisation procedure based on a genetic algorithm. A local FE analysis is conducted on a real turbine sub-model to identify potential crack initiation sites. Abstract: Fully reversed strain controlled low cycle fatigue and creep-fatigue interaction tests have been performed at ±0.7% strain amplitude and at three different temperatures (400 °C, 500 °C and 600 °C) to investigate the cyclic behaviour of a FV566 martensitic turbine steel. From a material point of view, the hysteresis mechanical responses have demonstrated cyclic hardening at the running-in stage and subsequent, hysteresis cyclic softening during the rest of the material life. The relaxation and energy behaviours have shown a rapid decrease at the very beginning of loading followed by quasi-stabilisation throughout the test. A unified, temperature- and rate-dependent viscoplastic model was then developed and implemented into the Abaqus finite element (FE) code through a user defined subroutine (UMAT). The material parameters in the model were determined via an optimisation procedure based on a genetic solver. The multi-axial form of the constitutive model developed was demonstrated by analysing the thermo-mechanical responses of an industrial gas turbine rotor subjected to in-service conditions. A sub-modelling technique was used to optimise the FEA. A 2D global model of the rotor with a 3D sub-model of the second stage of the low pressure turbine were then analysed in turn. The complex transient stress and accumulated plastic strain fields were investigated under realistic thermo-mechanical fatigue loading (start-up and shut-down power plant loads). The sub-model was then used for local analysis leading to identification of potential crack initiation sites for the presented types of blade roots.